Intrapulmonary percussive ventilation for children with bronchiolitis on non-Invasive Ventilation support - Yuval Cavari; Tal Levy Shlomo; Eitan Neeman; Ben Taragin; Michal Leder; Shaked Yarza; Isaac Lazar (Open Journal of Pediatrics and Child Health - Peertechz Publications, 2022)
Objective: Pediatric Intensive Care (PICU) admission of children with bronchiolitis as well as the use of Non-Invasive Ventilation (NIV) are increasing. The current treatment for bronchiolitis is supportive, and there are no specific studies addressing this group of severe bronchiolitis patients supported with NIV. Intrapulmonary Percussive Ventilation (IPV) is a lung recruitment physical therapy technique used in our PICU to augment lung aeration and improve gas exchange. We hypothesized that IPV treatment can be used to improve the clinical course of infants on NIV support suffering from bronchiolitis.  Design: A prospective, open, randomized study. Setting: Single-center Pediatric ICU Patients: Children less than 2 years old admitted to our PICU between November 2016 and April 2018 with a diagnosis of bronchiolitis who were prescribed noninvasive positive pressure ventilation as their sole respiratory treatment modality Interventions: Patients were randomly assigned to two intervention groups: IPV vs. control (standard treatment). Measurements and main results: Thirty-eight infants with bronchiolitis treated with NIV support were randomized into two groups. The probability of a superior outcome (less chance of invasive mechanical ventilation and fewer PICU days) was 62.7% (95% CI, 45%-77%, p = 0.18) in the IPV group compared to the control group. Among the IPV group, there were no failures that required intubation in comparison to three intubations (13.6%) among the control group (p = 0.24). For the IPV group, the PICU length of stay (LOS) was 4.13 ± 2.45 days, compared to 6.18 ± 4.72 for the inhalation group. This difference was not statistically significant. Conclusions: In this single-center study, the use of IPV had no adverse reactions. The study failed to show a statistically significant effect of IPV treatment on the course of hospitalization of patients with bronchiolitis on NIV support in the PICU. Trial registration: Clinical Trials.gov NCT03037801.